Intergenerational Proximity to Aging Parents and Depression Among Married Persons in China. (March 2023) - Fan, Jin; Zhang, Weiguo; Mi, Hong
Using data from China Health and Retirement Longitudinal Study ( N = 3864), we examined the relationship between proximity to aging parents and depression among middle-aged (45–64 years) married individuals in China. Our study depicted and explained the declining coresident rate and showed a majority of adult children live separately from their parents. Children living in different households had higher levels of depression than coresident children, including those living adjacently. Furthermore, having a coresident spouse increased the levels of depression of sons living in an adjacent dwelling and in the same city, and reduced the levels of depression of daughters living farther away. More intergenerational economic support increased the levels of depression of daughters living in an adjacent dwelling. These findings may offer a reference for married adult children to reconstruct intergenerational proximity and adjust intergenerational relations.